PENGARUH INVESTASI AKTIVA TETAP TERHADAP LABA BERSIH PADA PERUSAHAAN PERKEBUNAN KELAPA SAWIT YANG TERDAFTAR DI BURSA EFEK INDONESIA - Abel Malia; Johandri Iqbal; Pramesti Nurul Adinda (Journal of Applied Accounting And Business, 2025)
The influence of fixed asset investment on net profit of oil palm plantation companieslisted on the Indonesia Stock Exchange in 2019-2023. The data used in this study are secondary data, namely data obtained from the Indonesia Stock Exchange of companies listed on the Indonesia Stock Exchange (IDX) in 2019-2023. Data analysis uses quantitative data. Data analysis uses multiple linear regression methods. The results of the research show that fixed asset investment has a partial effect on net profits in oil palm plantation companies listed on the Indonesia Stock Exchange (IDX) in 2019-2023. And simultaneously fixed asset investment on net profit in oil palm plantation companies listed on the (IDX) in 2019-2023.